Thin Film Electrodes for Anodic Stripping Voltammetry: A Mini-Review - Wygant, Bryan R.; Lambert, Timothy N. (Frontiers in Chemistry, 2022)
Anodic stripping voltammetry (ASV) is a powerful electrochemical analytical technique that allows for the detection and quantification of a variety of metal ion species very low concentrations in aqueous media. While early, traditional ASV measurements relied on macroscopic electrodes like Hg drop electrodes to provide surfaces suitable for plating/stripping, more recent work on the technique has replaced these electrodes with thin film metal electrodes generated in situ. Such electrodes are plated alongside the analyte species onto the surface of primary electrode, producing a composite metal electrode from which the analyte(s) can then be stripped, identified, and quantified. In this minireview, we will explore the development and use of these unique electrodes in a variety of different applications. A number of metals (e.g. Hg, Bi, Sn, etc.) have shown promise as thin film ASV electrodes in both acidic and alkaline media, and frequently multiple metals in addition to the analyte of interest are deposited together to optimize the plating/stripping behavior, improving sensitivity. Due to the relatively simple nature of the measurement and its suitability for a wide range of pH, it has been used broadly: to measure toxic metals in the environment, characterize battery materials, and enable biological assays, among other applications. We will discuss these applications in greater detail, as well as provide perspective on future development and uses of these thin film electrodes in ASV measurements.